محافظ الحسابات ودوره في تعزيز جودة ومصداقية الكشوف المالية - قدوري, يسرى (My University, 2021)
The study aims to know the role of the auditor in enhancing the reliability of the financial statements and this is what was stated in Law 08-91 issued in 1991 related to the profession under study and Law 01-10 of June 29, 2010 repealed this law. Where the study dealt with the concept of the auditor, his missions and responsibilities when he performs his task, he has to go through certain stages to complete his work, as we have relied in our study on the financial statements and financial reports of the account auditor and some personal interviews of the account auditor. The personal interviews also enabled us to perform some of the professionals from auditor and certified accountants, and one of the most important aspects that affect the task is the international auditing standards ISA and the Algerian auditing standards NAA. The study concluded that the account auditor has a role in the reliability of financial statements, by approving these accounts or not certifying them, thus highlighting this role played by the account auditor